The relevance of livestock husbandry in the context of food security: a bibliometric outlook of research studies from 1938 to 2020 - Idamokoro, Emrobowansan Monday (Frontiers in Sustainable Food Systems, 2023)
The present study aimed to report knowledge based outcomes on global studies of livestock farming as a tool to address food security, while considering the recurring problems caused by mal-nutrition and hunger among vulnerable persons especially in developing countries. A total of 2012 scientific peer reviewed studies was retrieved in a BibTeX design for analysis using bibliometric collections in R studio software. The result obtained from the software included among others, authors, keywords plus, citations, collaborations, affiliations, journals, countries impact and key words. Published peer-reviewed dis coveries on livestock husbandry as related to food security gathered from Scopus and web of science (WOS) data bank were used with a rise in knowledge based findings of a yearly progression of 15.04 % during the timespan of the investigation. The result of the investigation revealed that, USA was ranked first in position with an aggregate of 236 publications (including, Single Country Publications (SCP) = 225 and Multiple Country Publications (MCP) = 11), and a huge international scientific effect with the highest article citations (n = 9138). The most frequently used authors’ keywords in the present research niche area were food security (n= 475), livestock (n = 123), agriculture (n =100), climate change (n = 99), sustainability (n = 55), cattle (n = 40), nutrition (n = 37), which gave a clear direction on related research studies on how livestock production can be used to enhance food security. The study in consideration presented an international picture that addresses the pool of knowledge based peer reviewed findings on livestock production research and its significance to food security, while giving a clue for more investigations in this research niche area. It is of high essence to emphasise that the current findings solely focused on prime areas of livestock production as related to food security research, thus, it is anticipated that novel empirical research work and potential scientific findings would give novel understanding and precision on livestock husbandry as a possible instrument to tackle the challenges of food security as new discoveries emerges.